Glaucoma severity affects diffusion tensor imaging (DTI) parameters of the optic nerve and optic radiation - Sidek, S.; Ramli, N.; Rahmat, K.; Ramli, N.M.; Abdulrahman, F.; Tan, L.K. (2014)
Objectives: To evaluate whether MR diffusion tensor imaging (DTI) of the optic nerve and optic radiation in glaucoma patients provides parameters to discriminate between mild and severe glaucoma and to determine whether DTI derived indices correlate with retinal nerve fibre layer (RNFL) thickness. Methods: 3-Tesla DTI was performed on 90 subjects (30 normal, 30 mild glaucoma and 30 severe glaucoma subjects) and the FA and MD of the optic nerve and optic radiation were measured. The categorisation into mild and severe glaucoma was done using the Hodapp-Parrish-Anderson (HPA) classification. RNFL thickness was also assessed on all subjects using OCT. Receiver operating characteristic (ROC) analysis and Spearman's correlation coefficient was carried out. Results: FA and MD values in the optic nerve and optic radiation decreased and increased respectively as the disease progressed. FA at the optic nerve had the highest sensitivity (87) and specificity (80). FA values displayed the strongest correlation with RNFL thickness in the optic nerve (r = 0.684, p <= 0.001) while MD at the optic radiation showed the weakest correlation with RNFL thickness (r = -0.360, p <= 0.001). Conclusions: The high sensitivity and specificity of DTI-derived FA values in the optic nerve and the strong correlation between DTI-FA and RNFL thickness suggest that these parameters could serve as indicators of disease severity. (C) 2014 Published by Elsevier Ireland Ltd.